The added prognostic values of baseline PET dissemination parameter in patients with angioimmunoblastic T‐cell lymphoma. Issue 1 (29th November 2022) - Gong, Huanyu; Tang, Bo; Li, Tiannv; Li, Jianyong; Tang, Lijun; Ding, Chongyang
Abstract: To explore the prognostic values of baseline 2‐deoxy‐2‐[ 18 F] fluoro‐D‐glucose (FDG) positron emission tomography/computed tomography (PET/CT) dissemination parameter in angioimmunoblastic T‐cell lymphoma (AITL) and its added values to total metabolic tumour volume (TMTV). Eighty‐one AITL patients with at least two FDG‐avid lesions in baseline PET/CT were retrospectively included. PET parameters including TMTV and the distance between the two lesions that are the furthest apart (Dmax) were obtained. Univariate Cox analysis showed that both Dmax and TMTV were risk factors for progression‐free survival (PFS) and overall survival (OS). Multivariate Cox analysis models of different combinations showed that high Dmax (> 65.7 cm) could independently predict both PFS and OS, while high TMTV (>456.6 cm 3 ) was only significant for OS. A concise PET model based on TMTV and Dmax can effectively risk‐stratify patients. PFS and OS rates were significantly lower in patients with high Dmax and high TMTV than in patients with low Dmax and low TMTV (3‐year PFS rate: 15.0% vs. 48.7%, p  = 0.001; 3‐year OS rate: 27.6% vs. 79.0%, p  < 0.001). Dmax can directly reflect the disease dissemination characteristic and has a significant prognostic value for FDG‐avid AITL patients. It has the potential to be introduced into new risk stratification models for tailored treatment.